Effect of dietary supplementation with Brevibacillus laterosporus on broiler growth performance, meat quality and gut microbiome - Han, Haixia; Fu, Li; Wang, Jie; Sun, Yan; Cao, Dingguo; Lei, Qiuxia; Zhou, Yan; Li, Fuwei; Liu, Wei; Li, Dapeng; Hao, Dan; Liu, Jie (Frontiers in Microbiology, 2025)
This study aimed to investigate the effects of Brevibacillus laterosporus (B. laterosporus) supplementation on growth performance, carcass traits, antioxidant capacity, and cecal microbiota in broilers. A total of 320 one-day-old YS909 male broilers were randomly assigned to four dietary groups: control (CON), low-dose (LBL, 100 mg/kg), medium-dose (MBL, 300 mg/kg), and high-dose (HBL, 500 mg/kg) B. laterosporus supplementation (n = 8 replicates/group, 10 chicks/replicate). Growth performance, carcass traits, antioxidant capacity, and cecal microbiota/metabolites (MBL vs. CON) were analyzed. Dietary supplementation with B. laterosporus significantly decreased the feed intake / weight gain (F/G) in LBL (22–42 d and 1–42 d), MBL (22–42 d) and HBL (22–42 d) groups. Both MBL and HBL groups showed higher semi-eviscerated percentages than the control. The MBL group had a significantly increased eviscerated percentage. The LBL group had a significantly increased breast muscle percentage. Specifically, the HBL group exhibited a notable increase in muscle C18:3n3 content, and a significant decrease in muscle C18:1n9t and C20:3n3 content. The LBL group saw significant reductions in the proportion of C18:1n9t and C20:1. Additionally, the MBL group experienced significant decreases in the proportions of C18:3n3, C20:3n3 and C20:4n6. Dietary supplementation with B. laterosporus significantly enhanced the oxidative stress resistance of serum by decreasing malondialdehyde (MDA) levels and increasing glutathione peroxidase (GSH-PX) and total antioxidant capacity (T-AOC). 16S ribosomal DNA and metabolome sequencing of cecum contents was conducted for the MBL and CON groups. This analysis demonstrated significant increases in α-diversity indices in the MBL group. There was an increased relative abundance of Firmicutes and a decreased relative abundance of Bacteroidetes and Proteobacteria in the MBL group. In addition, the shifts of the cecal microbial community lead to the alteration of metabolites of the cecum including amino acid and lipid. In conclusion, dietary supplementation with medium-dose B. laterosporus enhanced broiler carcass traits and antioxidant status by modulating cecal microbiota and metabolites, demonstrating its potential as an effective feed additive.